Impaired Development and Competitive Refinement of the Cortical Frequency Map in Tumor Necrosis Factor-α-Deficient Mice. (28th February 2013) - Yang, Sungchil; Zhang, Li S.; Gibboni, Robert; Weiner, Benjamin; Bao, Shaowen
Abstract : Early experience shapes sensory representations in a critical period of heightened plasticity. This adaptive process is thought to involve both Hebbian and homeostatic synaptic plasticity. Although Hebbian plasticity has been investigated as a mechanism for cortical map reorganization, less is known about the contribution of homeostatic plasticity. We investigated the role of homeostatic synaptic plasticity in the development and refinement of frequency representations in the primary auditory cortex using the tumor necrosis factor-α (TNF-α) knockout (KO), a mutant mouse with impaired homeostatic but normal Hebbian plasticity. Our results indicate that these mice develop weaker tonal responses and incomplete frequency representations. Rearing in a single-frequency revealed a normal expansion of cortical representations in KO mice. However, TNF-α KOs lacked homeostatic adjustments of cortical responses following exposure to multiple frequencies. Specifically, while this sensory over-stimulation resulted in competitive refinement of frequency tuning in wild-type controls, it broadened frequency tuning in TNF-α KOs. Our results suggest that homeostatic plasticity plays an important role in gain control and competitive interaction in sensory cortical development.